RTHP-10. LESS IS MORE OR BIGGER IS BETTER? RADIATION TREATMENT VOLUME FOR GLIOBLASTOMA PATIENTS DOES NOT IMPACT SURVIVAL. (5th November 2018) - Song, Andrew; Gowda, Sonia; Werner-Wasik, Maria; Bar-Ad, Voichita; Kim, Lyndon; Glass, Jon; Judy, Kevin; Farrell, Christopher; Andrews, David; Shi, Wenyin
Abstract: PURPOSE: To investigate if the extent of the planning target volume (PTV) for glioblastoma (GBM) patients receiving adjuvant radiation treatment (XRT) has correlation with survival. METHODS: We retrospectively examined patients with newly diagnosed GBM received adjuvant radiation at our institution from 2011 to 2016. Our institution follows the RTOG guidelines for GBM volumes. We included 87 patients with sufficient follow up. We examined the treatment plan documents to determine the PTV treated to 46 Gy (PTV46) and 60 Gy (PTV60). We measured overall survival (OS) as well as progression-free survival (PFS). We performed summary statistics on baseline patient characteristics, Kaplan-Meier analysis for outcomes with log-rank tests to compare PTV subgroups as well as Cox regression analysis for treatment volume. RESULTS: Of the 87 patients for analysis, 42 were female and 45 were male. Median age was 61 y/o, with median follow-up of 16.6 months (range 2.6 to 61.1 months). For PTV46 analysis, 1 patient was excluded due to receiving whole brain radiation to 40 Gy before receiving cone down to total 60 Gy. Median PTV60 was 297.9 cc (120.04 to 907.6 cc) while median PTV46 was 452 cc (120.04 to 907.6 cc). OS at 1 year was 67.8% and at 2 years was 32.2%, with median OS of 16.6 months. PFS at 6 months was 58.6% and at 1 year was 27.6%, with median time to progression of 6.8 months. On Cox regression analyses, neither PTV46 nor PTV 60 were statistically significant correlated with OS (p=0.11 and 0.68) and PFS (p=0.54 and 0.64). On log rank test, neither PTV46 nor PTV60 subgroups have any statistically significant survival differences, for PFS or OS. CONCLUSION: Extent of PTV does not appear to have an impact on recurrence or survival for GBM. Further validation with an independent dataset is warranted.